Photodecay of guaiacol is faster in ice, and even more rapid on ice, than in aqueous solution. Issue 8 (16th July 2020) - Hullar, Ted; Bononi, Fernanda C.; Chen, Zekun; Magadia, Danielle; Palmer, Oliver; Tran, Theo; Rocca, Dario; Andreussi, Oliviero; Donadio, Davide; Anastasio, Cort
Abstract : Guaiacol photodegradation rate constants in solution, liquid-like regions in ice (frozen solutions), and at the air–ice interface (vapor-deposited to snow). Abstract : Snowpacks contain a wide variety of inorganic and organic compounds, including some that absorb sunlight and undergo direct photoreactions. How the rates of these reactions in, and on, ice compare to rates in water is unclear: some studies report similar rates, while others find faster rates in/on ice. Further complicating our understanding, there is conflicting evidence whether chemicals react more quickly at the air–ice interface compared to in liquid-like regions (LLRs) within the ice. To address these questions, we measured the photodegradation rate of guaiacol (2-methoxyphenol) in various sample types, including in solution, in ice, and at the air–ice interface of nature-identical snow. Compared to aqueous solution, we find modest rate constant enhancements (increases of 3- to 6-fold) in ice LLRs, and much larger enhancements (of 17- to 77-fold) at the air–ice interface of nature-identical snow. Our computational modeling suggests the absorption spectrum for guaiacol red-shifts and increases on ice surfaces, leading to more light absorption, but these changes explain only a small portion (roughly 2 to 9%) of the observed rate constant enhancements in/on ice. This indicates that increases in the quantum yield are primarily responsible for the increased photoreactivity of guaiacol on ice; relative to solution, our results suggest that the quantum yield is larger by a factor of roughly 3–6 in liquid-like regions and 12–40 at the air–ice interface.